2022
DOI: 10.1136/jim-2021-002161
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Therapy in Respiratory Illness: Bench to Bedside

Abstract: Each year, hundreds of millions of individuals are affected by respiratory disease leading to approximately 4 million deaths. Most respiratory pathologies involve substantially dysregulated immune processes that either fail to resolve the underlying process or actively exacerbate the disease. Therefore, clinicians have long considered immune-modulating corticosteroids (CSs), particularly glucocorticoids (GCs), as a critical tool for management of a wide spectrum of respiratory conditions. However, the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 281 publications
(543 reference statements)
0
7
0
Order By: Relevance
“…In the treatment of CEP, the recommended initial OCS dose is 0.5 mg/kg, and because the patient weighed 49.4 kg, 25 mg/day would usually be used ( 1 ). However, this case was complicated by uncompensated LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of CEP, the recommended initial OCS dose is 0.5 mg/kg, and because the patient weighed 49.4 kg, 25 mg/day would usually be used ( 1 ). However, this case was complicated by uncompensated LC.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma and chronic eosinophilic pneumonia (CEP) can be comorbid, and studies have shown that oral corticosteroids (OCSs) are successful in treating CEP ( 1 ). The metabolism of corticosteroids (CSs) in the liver is impaired in patients with severe liver cirrhosis (LC), and CS may further aggravate liver function and increase the risk of impaired consciousness by elevating the amount of circulating NH 3 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…For patients with contraindications or who failed prevention, thrombosis was still an important factor affecting prognosis. Steroid, as a type of anti-inflammatory drug, can effectively promote the absorption of pneumonia 14. In clinical practice, we often prescribed the dose of steroid according to the severity (determined by patients’ symptoms, imaging manifestations and blood gas indexes).…”
Section: Discussionmentioning
confidence: 99%
“…Modulating neutrophilic inflammation has historically been challenging in respiratory medicine 1,2 despite an expanding pool of immunomodulators available for clinical use [3][4][5][6] . A major bottleneck has been the lack of preclinical screening tools that adequately capture human-specific neutrophil responses such as priming while in the circulation, pathological recruitment into tissues, and the secondary acquisition of dysfunctional states therein 2,[7][8][9] .…”
Section: Introductionmentioning
confidence: 99%